Physiological and Histological Studies on the Effect of Hydrocortisone on Kidneys of Rabbits - Al-Zail, Nura I.; Aboalhaj , Abdusalam M.; Shuaib, Zainab A. (Al-Mukhtar Journal of Sciences, 2017)
This study aimed to test the effect of hydrocortisone sodium succinate drug on blood serum components and kidneys tissues in white rabbits.The experiment included 30 male rabbits weighing between 1500-2500g. They were divided into 4 control and treated groups, for different periods of time, depending on the duration of injection. Treatment of the rabbits with hydrocortisone dose of 10 mg/kg daily did not lead to change in the weights of rabbits treated for a week. Non significant increase occurred in the weights of rabbits treated for two weeks and treated gradually, but in sudden treated group a non significant decrease in rabbits weights was recorded in comparison with their weights before injection .A significant increase in the concentration of urea, creatinine, total serum protein, albumin, sodium and potassium ions after treatment for a week, but a significant reduction was noted in the concentration of urea and no significant difference was noted in the concentration of creatinine, sodium and potassium ions after treatment for two weeks. While there were a significant increase in the total serum protein and albumin after two weeks of treatment. Noting that, in the suddeny treated group, the biochemical parameters did not change compared to that present in the two weeks treated rabbits. While, in the gradually treated group, most of the biochemical parameters returned to their normal values .Histological examination of the renal cortex showed acidophilic material accumulated in the lumina of some distal convoluted tubules in the group treated for two weeks. The renal medulla also showed the presence of the same material inside the collecting tubules in the both treated groups. With the increase of the duration of treatment; the intracytoplasmic vacuoles appeared in many of the cells lining the collecting tubules. The same histopathological changes were observed in the kidneys of rabbits that their treatment was suddenly stopped, as well as the group that their treatment was gradually stopped, but these changes became low in the last group.